Review of necessary thermophysical properties and their sensivities with temperature and electrolyte mass fractions for alkaline water electrolysis multiphysics modelling. (22nd February 2019) - Le Bideau, Damien; Mandin, Philippe; Benbouzid, Mohamed; Kim, Myeongsub; Sellier, Mathieu
Abstract: This article presents an exhaustive review of the transport properties necessary for the multiphysics modelling of alkaline water electrolyzer. This article provides experimental data and the correlations needed to calculate thermos-physical properties such as electrical conductivity, density, viscosity, heat capacity, heat and mass transfer diffusion coefficients as a function of temperature and electrolyte mass fraction for two classical alkaline electrolytes (KOH, NaOH). Thus, the different boundary layers growing on the electrodes can be calculated with precision. Different interpolation models from various authors are compared to raw experimental data. The goal of this article is to give to the modeler the correlations needed for the simulation of alkaline water electrolysis. Highlights: Complete thermophysical properties set for alkaline water electrolyzers modelling. Properties given with temperature and alkaline species concentration sensitivities. Rigorous triple two-phase boundary layers at both electrodes calculation allowed. Better primary, secondary or ternary current distribution modelling at electrodes. Thermophysical properties discrepancies among different authors evaluated.